KEMAMPUAN BACA-TULIS SISWA DISLEKSIA - Hidayah, Rifa (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2009)
The purposes of this research are (1) comprehending the reading and writing ability of child of dyslexia, (2) Reading and writing resistant factor, and (3). Study model for child of dyslexia. The result of the research shows; (1). Reading ability and writes ability of dyslexia are low, (2). The factor influencing the reading disability are (a). disfunction nerve system, (b). Slow development and lacking of nutrition, (c). Slow short term memory, (d). Lack of family support and supporting facilities for study, (e). less mature of physical, emotional and social. (3). Learning model. In general, Learning process for child of dyslexia in class is equal to other children, but there is special treatment for dyslexia that is they have special requirement, such as special teacher, method and private space and time especially. The treatment was specially given for the improvement of reading and writing ability of child of dyslexia.